Islamic Songs in Indonesia: Expressing and Popularizing Piety Through Popular Music - Abdul, Hadi; Himiyatun Najah; Anisa Fitriani; Diva Latifa Praptini; Hayatul Aeni; Asril Zulkipli; Asril Zulkipli; M. Ridwan Zaen (BADA’A: Jurnal Ilmiah Pendidikan Dasar, 2023)
This article deals with the emergence of Islamic songs produced by some prominent Indonesian pop music bands. Particular attention is paid to their music and songs based on several reasons; firstly, their music genre is quite different from what the so-called Islamic mainstream songs which previously took the form of Arabic-inclined music, such as gambus, qasidah, and nasheed with exclusively and explicitly conveyed Islamic messages towards the audiences. This later genre of Islamic songs utilizes pop music and even rock music to perform their creativity. Although according to the artists their ultimate goal in producing Islamic songs is to celebrate magnificent of Islam (syi’ar Islam) or·in many ways for dakwah (preaching), the way they convey the message is not necessarily the same with what has been known as mainstream Islamic songs. They choose their own way that is deemed to be more popular and entertaining than before. Secondly, the production of this genre of Islamic song involves the major label companies which consider it as promising and profitable business. Formerly, Islamic songs had hardly been produced by major labels except popular bands like Bimbo. In this regard, Islamic songs were considered as countrified (kampungan) and preferred by low class society. Thirdly, this music generally targets young people in urban regions as its main customers. This is of course by modifying musical style and performance that meets the need and desires of these young people through modern popular music genre.